A tri-site fluorescent probe for simultaneous sensing of hydrogen sulfide and glutathione and its bioimaging applications. Issue 2 (21st December 2017) - Chen, Fengzao; Han, Deman; Liu, Heng; Wang, Shengfu; Li, Kai-Bin; Zhang, Siqi; Shi, Wei
Abstract : Hydrogen sulfide (H2 S) and biothiol molecules, such as glutathione (GSH), cysteine (Cys), and homocysteine (Hcy), play an important role in biology. Abstract : Hydrogen sulfide (H2 S) and biothiol molecules, such as glutathione (GSH), cysteine (Cys), and homocysteine (Hcy), play an important role in biology. However, understanding the complicated relationship between H2 S and biothiols remains an enormous challenge owing to the difficulty in sensing H2 S and biothiols simultaneously. Therefore, the development of probes for detecting H2 S and biothiols is of great importance in biological science. In this work, we reported a novel fluorescent probe for the sensitive and selective detection of H2 S and glutathione (GSH) simultaneously in different buffer solutions. The key design principle is based on a coumarin as the fluorophore structuring a fluorescent probe with three potential sites which could react with H2 S and biothiols. This probe displays a rapid response with highly sensitive and selective detection of H2 S and GSH (the detection limit of 75 nM and 280 nM, respectively). Moreover, with the assistance of a confocal fluorescence microscope, we demonstrated that the probe can be successfully applied for imaging H2 S and GSH in MCF-7 cells.